(untitled) (Journal of Medical Device Technology, 2023)
After athletic injuries, cold techniques are used commonly, with clear physiological effects. The main theory about the advantages of immersion in cold water is that it decreases skeletal muscle inflammation. This study was to design the electronic part of smart portable ice bath monitoring system for the athletes to use after their exercises. The design can capture cold water temperature reading and heart rate precisely during the therapy. The readings also were used to give out notifications and alarm to prevent cold related diseases. Various of components were listed and only the most compatible with the design were chosen. The criteria of the components are small, light in weight and the most important is waterproof. To have the portable design of cold-water immersion easy to use and understand, a smartphone application was created by using MIT App inventor, thus giving the athlete a platform to monitor their heart rate data and aware of the benefit and disadvantage of cold-water immersion. Three independent subjects’ heart rates were recorded and compared to test the hypothesis that there is a significant difference in heart rate readings between the heart rate sensor and the Amazfit GTS 2. While three tests on the temperature of cold water were used to test the hypothesis that the temperature readings produced by temperature sensor and mercury thermometer had a significant difference. Response of the data from both tests were analysed by using a t-test. The results of both experiments revealed that the hypothesis was rejected, indicating that the heart rate sensor and temperature sensor are adequate for monitoring heart rate and cold-water temperature. They were displayed on the LCD display and the MIT app inventor application in a smartphone. The notification alarm is also effective. In conclusion, the study’s objectives have been achieved, and the design can be applied in cold water immersion therapy.